Next-Generation Cancer Biomarkers: Extracellular Vesicle DNA as a Circulating Surrogate of Tumor DNA - Amintas, Samuel; Vendrely, Véronique; Dupin, Charles; Buscail, Louis; Laurent, Christophe; Bournet, Barbara; Merlio, Jean-Philippe; Bedel, Aurélie; Moreau-Gaudry, François; Boutin, Julian; Dabernat, Sandrine; Buscail, Etienne (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are produced by healthy tissues and tumor cells and are released in various bodily fluids, including blood. They are limited by bilayer phospholipidic membranes and they carry a rich content in biomolecules. Their release cleanses the cells of their waste or serves as functional local and distant cell-cell communication, and molecular exchange particles. This rich and heterogeneous content has been given intense attention in cancer physiopathology because EVs support cancer control and progression. Because of their specific active cargo, they are being evaluated as carriers of liquid biopsy biomarkers. Compared to soluble circulating biomarkers, their complexity might provide rich information on tumor and metastases status. Thanks to the acquired genomic changes commonly observed in oncogenic processes, double-stranded DNA in EVs might be the latest most promising biomarker of tumor presence and complexity. This review will focus on the recent knowledge on the DNA inclusion in vesicles, the technical aspects of EV-DNA detection and quantification, and the use of EV-DNA as a clinical biomarker.